Vitamin D deficiency relation to sepsis, paediatric risk of mortality III score, need for ventilation support, length of hospital stay, and duration of mechanical ventilation in critically ill children: A meta‐analysis. Issue 4 (20th December 2020) - He, Mingyi; Cao, Tao; Wang, Jing; Wang, Changyuan; Wang, Zheng; Abdelrahim, Mohamed E. A.
Abstract: Introduction: Vitamin D deficiency in children is related to the augmented risk of bone illnesses, but its effect on critically ill children is still conflicting. This meta‐analysis study was performed to assess the relationship between vitamin D deficiency in children and sepsis, paediatric risk of mortality III score, need for ventilation support, length of hospital stay, and duration of mechanical ventilation in critically ill children. Methods: Through a systematic literature search up to June 2020, 16 studies with 2382 children, 1229 children of them with vitamin D deficiency, were found recording relationships between vitamin D deficiency and sepsis, paediatric risk of mortality III score, need for ventilation support, length of hospital stay, and/or duration of mechanical ventilation. Odds ratio (OR) with 95% confidence intervals (CIs) was calculated between vitamin D deficiency children to non‐vitamin D deficiency children on the different outcomes in critically ill children using the dichotomous or continuous methods with a random or fixed‐effect model. Results: The vitamin D deficiency children category had significantly higher sepsis (OR, 2.35; 95% CI, 1.19‐4.63, P = .01); paediatric risk of mortality III score (OR, 2.19; 95% CI, 1.13‐4.25, P = .02); higher length of hospital stay (OR, 4.26; 95% CI, 0.81‐7.70, P = .02); higher duration of mechanical ventilation (OR, 1.89; 95% CI, 0.22‐3.56, P = .03) compared with that in the non‐vitamin D deficiency children. However, the need for ventilation support in vitamin D deficiency children did not significantly differ from non‐vitamin D deficiency children (OR, 2.00; 95% CI, 0.98‐4.07, P = .06) with relatively higher results in vitamin D deficiency children. Conclusions: Vitamin D deficiency in children might have an independent relationship with higher sepsis, paediatric risk of mortality III score, length of hospital stay, and duration of mechanical ventilation. The relation was relative with a higher risk in need for ventilation support with vitamin D deficiency children. This relationship encouraged us to recommend testing vitamin D levels in all critically ill children and providing them with supplemental vitamin D as prophylaxis.